2022
DOI: 10.1186/s12957-022-02672-5
|View full text |Cite
|
Sign up to set email alerts
|

An mALBI-Child–Pugh-based nomogram for predicting post-hepatectomy liver failure grade B–C in patients with huge hepatocellular carcinoma: a multi-institutional study

Abstract: Objective Post-hepatectomy liver failure (PHLF) is a severe complication in patients with hepatocellular carcinoma (HCC) who underwent hepatectomy. This study aims to develop a nomogram of PHLF grade B–C in patients with huge HCC (diameter ≥ 10 cm). Methods We retrospectively collected clinical information of 514 and 97 patients who underwent hepatectomy for huge HCC at two medical centers between 2016 and 2021. Univariate and multivariate analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Therefore it is less accurate for the diagnosis of early occult cirrhosis, while its inclusion of intraoperative blood loss, like that of Xu, makes it difficult to assess PHLF preoperatively. Meanwhile, its inclusion of tumor size is subjective and without a stated criterion for judging ( 28 ). Chin developed a model to predict PHLF, but the model included patients with colorectal cancer with liver metastases who received preoperative neoadjuvant chemotherapy, and the model was not validated, so it is uncertain whether it can predict PHLF accurately in other data sets ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it is less accurate for the diagnosis of early occult cirrhosis, while its inclusion of intraoperative blood loss, like that of Xu, makes it difficult to assess PHLF preoperatively. Meanwhile, its inclusion of tumor size is subjective and without a stated criterion for judging ( 28 ). Chin developed a model to predict PHLF, but the model included patients with colorectal cancer with liver metastases who received preoperative neoadjuvant chemotherapy, and the model was not validated, so it is uncertain whether it can predict PHLF accurately in other data sets ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies have demonstrated, high levels of serum inflammatory markers are strongly associated with poor prognosis in cirrhosis and solid tumors. Cirrhosis is an important indicator for the preoperative evaluation of liver function and surgical feasibility and has been used as the final predictor by several PHLF prediction models, including reference nomogram [19,39,40]. Thus, it is not surprising that PCT and SII can improve the model's predictive ability of PHLF in patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports, the calculation formula for ALBI grade is as follows: ALBI score=(\log_{10} {Bilirubin}\times 0.66-0.085\times albumin), where the unit for bilirubin is µmol/L and albumin is g/L [21].…”
Section: Indicatorsmentioning
confidence: 99%
“…The ALBI and mALBI grades are classified and presented in Table 1 [21]. The neutrophil-lymphocyte ratio (NLR) is calculated as the number of neutrophils divided by the number of lymphocytes (NLR=\frac{neutrophil count}{lymphocyte count} ) [18].…”
Section: Indicatorsmentioning
confidence: 99%